2014
DOI: 10.1111/weng.12081
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' attitudes towards Korean English in South Korea

Abstract: This study explores the attitudes of English teachers, both Korean and non-Korean, towards 'Korean English' (KoE) in South Korea. Data about these attitudes were collected via 204 questionnaires and 25 post-survey individual interviews, from two major regions, Busan Gyeongnam and Seoul Gyeonggi, and were analysed both qualitatively and quantitatively. The results indicate that the majority of participants displayed a positive attitude towards KoE, especially regarding to the 'cognitive' component of attitude, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 37 publications
4
87
1
Order By: Relevance
“…Despite the overall resistance and negative attitudes shown by the study participants towards EIL/EFL at first, they later-after I had explained to them IEL/EFL-showed some kind of readiness to try out this kind of English as they viewed it as 'easy' and could work out well for developing their communication skills. Such degree of positive attitude and acceptance towards learning of EIL/ELF resonates with some previous studies (e.g., Ahn, 2014;Bernaisch & Koch, 2016) on attitudes of teachers and learners towards local varieties of English due to its high degree of intelligibility and easiness. Such findings suggest that teachers and learners should not shy away from trying out such non-standard mainstream variety of English.…”
Section: Conclusion Implications and Recommendations For Tesolsupporting
confidence: 89%
“…Despite the overall resistance and negative attitudes shown by the study participants towards EIL/EFL at first, they later-after I had explained to them IEL/EFL-showed some kind of readiness to try out this kind of English as they viewed it as 'easy' and could work out well for developing their communication skills. Such degree of positive attitude and acceptance towards learning of EIL/ELF resonates with some previous studies (e.g., Ahn, 2014;Bernaisch & Koch, 2016) on attitudes of teachers and learners towards local varieties of English due to its high degree of intelligibility and easiness. Such findings suggest that teachers and learners should not shy away from trying out such non-standard mainstream variety of English.…”
Section: Conclusion Implications and Recommendations For Tesolsupporting
confidence: 89%
“…This negative perspective toward non-native variants of English can be seen in previous studies whereby speakers felt embarrassed in speaking about their own varieties of English (Matsuda, 2000(Matsuda, , 2003Takeshita, 2010;Luo, 2016;Meilin & Xiaoqiong, 2015;Munro, Derwing & Morton, 2006;Young& Walsh, 2010). However, in this study some of the attitudinal changes regarding cognitive, affective and behavioral elements, similar to what Tokumoto and Shibata (2011) and Ahn (2014Ahn ( , 2017 identified, were noticeable among Indian and Iranian teachers.…”
Section: Discussionsupporting
confidence: 71%
“…For example, in Japan (McKenzie, 2008;Suzuki, 2011), in Korea (Ahn, 2014;McDonald & McRae, 2010;Young & Walsh, 2010), in Denmark (Ladegaard & Sachdev, 2006); in Greece (Sifakis, 2009;Sifakis&Sougari, 2005), in Taiwan (Huang, 2016;Luo, 2016), in Hong Kong (Zhang, 2013), in China (Meilin& Xiaoqiong, 2006, in Norway (Rindal 2010), in Europe (Groom, 2012) and in Iran (Sharifian, 2009(Sharifian, , 2010. Overall, these studies have shown tendencies concerning degree of awareness of other varieties of English, preferences towards these varieties, as well as their social and cultural meanings.…”
Section: Attitudes and Accentsmentioning
confidence: 99%
“…Research in this vein consistently demonstrates teachers’ and students’ entrenched perceptions that NS varieties are the sole acceptable models for English language learners, whereas localized varieties are inappropriate, undesirable, or unproductive targets (Ahn, , ; A. Matsuda, ; Young & Walsh, ), though there are isolated cases in which learners expressed disdain for NS standards (Sridhar & Sridhar, ). Native speaker biases are typically justified by reference to a range of elements that are held to exert an incontestable influence on the scope of possibilities in local teaching contexts.…”
Section: Literature Reviewmentioning
confidence: 98%